Zonal flows near marginal stability in drift wave transport. (1st May 2015) - Wang, G Q; Ma, J; Weiland, J
Abstract: The Dimits nonlinear upshift has for the first time been explained with good quantitative agreement. This was done with the reactive toroidal advanced fluid model. This is also the first time that the Dimits shift has been simulated in a transport code. The upshift of the critical gradient for transport is due to the fluid resonance, enhancing the zonal flow and the finite width is due to detuning of the resonance by the linear growth rate.